2007
DOI: 10.1002/nme.2204
|View full text |Cite
|
Sign up to set email alerts
|

Upper bound solution to elasticity problems: A unique property of the linearly conforming point interpolation method (LC‐PIM)

Abstract: I looked at this paper with interest, as it promised an upper bound solution, which apparently could not be related to some form of complementary potential energy and to statically admissible solutions, but these expectations were reduced, when I verified that in Figure 4, for a force-driven problem, the method could provide 'upper bounds' that are smaller than the exact solution.Nevertheless, in the abstract and at the beginning of Section 5. Theorem 3 proves that there is a bound of the exact solution, but o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
121
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 183 publications
(129 citation statements)
references
References 19 publications
8
121
0
Order By: Relevance
“…It has been found that the NS-FEM works well for the polygonal elements [24]. Because of its upper bound properties [24], and the ease of generating triangular (2D) and tetrahedron (3D) elements for complicated domains, it is used in this work for formulating our FEM for bioheat transfer problems. A brief introduction for the formulations of the triangular elements in 2D problems and tetrahedron elements in 3D problems is now presented.…”
Section: Briefing On the Ns-femmentioning
confidence: 99%
“…It has been found that the NS-FEM works well for the polygonal elements [24]. Because of its upper bound properties [24], and the ease of generating triangular (2D) and tetrahedron (3D) elements for complicated domains, it is used in this work for formulating our FEM for bioheat transfer problems. A brief introduction for the formulations of the triangular elements in 2D problems and tetrahedron elements in 3D problems is now presented.…”
Section: Briefing On the Ns-femmentioning
confidence: 99%
“…References [14,15] provide the same inequality (19) and proved that the strain energy computed with SFEM is also an upper bound on the exact strain energy, but only under the hypothesis that shape functions exist for exact solutions. Many numerical examples show that SFEM does give upper bounds on the true strain energy, except for some cases where the meshes are too coarse.…”
Section: Theoremmentioning
confidence: 84%
“…It has been found that in some situations the strain energy computed by SFEM bounds the exact strain energy from above [14][15][16]. This method stems from mesh-free finite element research and was first proposed to develop a stabilized nodal integration scheme for the Galerkin mesh-free method.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The smoothed strain field overcomes the problems associated with continuity of the approximation field over the problem domain through elimination of the need for the derivatives of the shape functions. Different smoothing domains can be adopted for the smoothing operation leading to different SPIMs [3][4][5][6]. The simplest SPIM is perhaps the cellbased SPIM (CSPIM) in which the cells of a triangular background mesh are used as the smoothing domains.…”
Section: Introductionmentioning
confidence: 99%